THE EFFECTIVENESS OF TEACHING MODULE COMPUTER BASED DRILLING MODEL AND PRACTICE IN IMPROVING LEARNING ACHIEVEMENT OF INDONESIAN LANGUAGE - Padlurrahman Padlurrahman; Muh. Jaelani Al-Pansori (Universitas Negeri Makassar, 2021)
This study aims to determine the effectiveness of the computer-assisted learning module for drill and practice model of Indonesian language learning in SMA/MA East Lombok District. This research includes development research through the stage of requirement analysis, limited sample testing and testing of action research settings. The research subject consists of teachers and SMA/ MA students in East Lombok district. Research Data is collected via questionnaire, observation sheets, tests, and interview guidelines. Data was analyzed using the component's anáolysis technique and continued with test-t analysis. The results showed that (1) th majority of teacher prepare the teaching materials independently than work collaboratively; (2) The result of learning Indonesian language through the use of a computer-assisted drill and practice based learning Module at each cycle increases, (3) There are differences in the results of Indonesian language learning between students who have been taught using a computer-assisted learning module drill and practice model with students who are taught without using a computer-assisted learning Module drill and practice model, and (4) students ' responses to learning modules developed and are in a good category.